Modulation of K+ channels in Vicia stomatal guard cells by peptide homologs to the auxin-binding protein C terminus. - Thiel, G; Blatt, MR; Fricker, M; White, I; Millner, P (1993)
Transduction of the auxin stimulus in plants is thought to entail binding of the hormone to a soluble auxin-binding protein (ABP) outside the cell and subsequent interaction between this auxin-protein complex and an integral membrane receptor ("docking") protein that couples the signal across the plasma membrane. To explore the structural requirements for ABP function, synthetic peptides were prepared to the amino acid sequences of the predicted surface domains of ABPzm1, the dominant ABP from Zea. Biological function was assayed under voltage clamp, monitoring the ability of the peptides to evoke auxin-related modulations in inward- (IK,in) and outward-rectifying (IK,out) K+ channel activities of Vicia guard cells in the absence of added auxin. Only the peptide corresponding to the C-terminal domain of ABPzm1 was active. The dominant response was an inactivation of IK,in, although the peptide also evoked an activation of IK,out. Inactivation of IK,in was complete within 20-30 s and was fully reversible, was marked by a slowing of voltage-dependent activation and deactivation, and was dependent on peptide concentration (K1/2, 16 +/- 6 microM). Buffering cytoplasmic-free [Ca2+] with EGTA had no effect on IK,in response to the peptide. However, virtually complete and reversible block of the response was achieved when cytoplasmic pH (pHi) was brought under experimental control using the weak acid butyrate. Parallel measurements of pHi using the fluorescent dye 2',7'-bis(2-carboxyethyl-5(6)-carboxyfluorescein (BCECF) and dual-wavelength laser-scanning confocal microscopy demonstrated that the C-terminal peptide evoked rapid and reversible cytoplasmic alkalinizations of 0.4 +/- 0.1 pHi unit and confirmed the antagonism of the pHi response in the presence of butyrate. These, and comparable results with the auxins indole acetic acid and 1-naphthyleneacetic acid, implicate the C-terminal domain of ABPzm1 in auxin-ABP coupling to pHi and an associated intracellular signaling cascade.